Nanoparticle-loaded microcapsules providing effective UV protection for Cry1Ac. (17th November 2021) - Zhang, Yongjing; Zhang, Aijing; Li, Mengyuan; He, Kanglai; Guo, Shuyuan
Abstract: Aim: To prepare several novel microcapsules using chitosan (Cs) and Alginate (Alg) as coating materials, and nano-ZnO, nano-SiO2, nano-TiO2 as UV protective agents for improving UV resistance of Cry1Ac. Methods: Microcapsules were prepared by the layer-by-layer (LbL) self-assembly technique and electrostatic adsorption. The morphologies were observed by scanning electron microscopy (SEM), and the stability under UV radiation was studied by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and bioassay. Results: SEM showed that nano-ZnO and nano-TiO2 could be adsorbed on the negatively charged MC with the outermost layer being Alg, while nano-SiO2 could be adsorbed on the positively charged MC with Cs as the outermost layer. SDS-PAGE and bioassay showed that nano-ZnO and nano-SiO2 could provide effective UV protection after 8 h UV irradiation ( p  > 0.05), and nano-TiO2 could provide effective UV protection after 4 h UV irradiation ( p  > 0.05). Conclusion: The microcapsules loaded with nanoparticles provided excellent UV resistance for Cry1Ac.